Effects of hypoxic preconditioning on synaptic ultrastructure in mice. Issue 1 (24th September 2014) - Liu, Yi; Sun, Zhishan; Sun, Shufeng; Duan, Yunxia; Shi, Jingfei; Qi, Zhifeng; Meng, Ran; Sun, Yongxin; Zeng, Xianwei; Chui, Dehua; Ji, Xunming
ABSTRACT Hypoxic preconditioning (HPC) elicits resistance to more drastic subsequent insults, which potentially provide neuroprotective therapeutic strategy, but the underlying mechanisms remain to be fully elucidated. Here, we examined the effects of HPC on synaptic ultrastructure in olfactory bulb of mice. Mice underwent up to five cycles of repeated HPC treatments, and hypoxic tolerance was assessed with a standard gasp reflex assay. As expected, HPC induced an increase in tolerance time. To assess synaptic responses, Western blots were used to quantify protein levels of representative markers for glia, neuron, and synapse, and transmission electron microscopy was used to examine synaptic ultrastructure and mitochondrial density. HPC did not significantly alter the protein levels of astroglial marker (GFAP), neuron‐specific markers (GAP43, Tuj‐1, and OMP), synaptic number markers (synaptophysin and SNAP25) or the percentage of excitatory synapses versus inhibitory synapses. However, HPC significantly affected synaptic curvature and the percentage of synapses with presynaptic mitochondria, which showed concomitant change pattern. These findings demonstrate that HPC is associated with changes in synaptic ultrastructure. Synapse 69:7–14, 2015. © 2014 Wiley Periodicals, Inc.